2018
DOI: 10.21474/ijar01/6234
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Efficacy and Safety Analysis of Zybev (Biosimilar of Bevacizumab) Use at Tertiary Eye Care Centres in India: Spectra Trial.

Abstract: Purpose:The purpose of this study was to evaluate the efficacy and safety profile of intravitreal injection of bevacizumabbiosimilar (Zybev) for various retinal neovascular conditions. Methods: Retrospective analysis was carried out on 108 injections which were administered with intravitrealZybev injection at different tertiary eye care centers in India. The injections were administered for various indications such as wet age-related macular degeneration (AMD), diabetic macular edema (DME), and retinal vein oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…[ 9 , 10 ] Warudkar et al . [ 11 ] showed the safety and efficacy of intravitreal injection of Zybev (Cadila Healthcare, India) as a bevacizumab bio-similar product for macular edema secondary to retinal vascular diseases. Mirshahi et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 10 ] Warudkar et al . [ 11 ] showed the safety and efficacy of intravitreal injection of Zybev (Cadila Healthcare, India) as a bevacizumab bio-similar product for macular edema secondary to retinal vascular diseases. Mirshahi et al .…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Afterward, Warudkar et al showed the safety and efficacy of intravitreal injection of Zybev (Cadila Healthcare, India) as a bevacizumab biosimilar for macular edema secondary to retinal vascular diseases. [15] As the patent of Avastin has recently expired, it is speculated that its biosimilars will soon grow in number. [10,11] Biosimilar production is >25% cheaper than that of the reference drug.…”
Section: Discussionmentioning
confidence: 99%